Data-Driven Approach for Teaching Arabic as a Foreign Language: Eygpt (Journal of the College of Education for Women, 2020)
Corpus linguistics is a methodology in studying language through corpus-based research. It differs from a traditional approach in studying a language (prescriptive approach) in its insistence on the systematic study of authentic examples of language in use (descriptive approach).A “corpus” is a large body of machine-readable structurally collected naturally occurring linguistic data, either written texts or a transcription of recorded speech, which can be used as a starting-point of linguistic description or as a means of verifying hypotheses about a language. In the past decade, interest has grown tremendously in the use of language corpora for language education. The ways in which corpora have been employed in language pedagogy can be divided into two main categories: indirect and direct application. In the former corpora are used in designing and developing the syllabuses, dictionaries, tests, and teaching materials, while later, corpus data are used for data-driven learning and what is known as grammar safari. So this research aims at employing corpus data in teaching Arabic grammar. Functional syntactic analysis of corpus is a must for this purpose, so Quranic corpus is the most appropriate one. In this paper,I examined the specification phenomenon (التمييز) in Quranic corpus and compared the descriptive and prescriptive approaches in teaching causative object as a grammatical phenomenon in Arabic.